In-line coupling of supported liquid membrane extraction across nanofibrous membrane to capillary electrophoresis for analysis of basic drugs from undiluted body fluids - Dvořák, Miloš; Kubáň, Pavel (Electrophoresis, 2019)
Planar polyamide 6 nanofibrous membrane was for the first time used in direct coupling of supported liquid membrane (SLM) extraction to CE analysis. Disposable microextraction device with the nanofibrous membrane was preassembled and stored for immediate use. The membrane in the device was impregnated with 1 µL of 1-ethyl-2-nitrobenzene and the device was subsequently filled with 10 µL of acceptor solution (10 mM HCl) and 15 µL of donor solution (sample). The device was in-line coupled to CE system for selective extraction and direct injection, separation and quantification of model basic drugs (nortriptyline, haloperidol, loperamide and papaverine) from standard saline solutions (150 mM NaCl) and from undiluted human body fluids (urine and blood plasma). Compared to standard polypropylene supporting material, the nanofibrous membrane demonstrated superior characteristics in terms of lower consumption of organic solvents, constant volumes of operational solutions, full transparency and possibility to preassemble the devices. Extraction parameters were better or comparable for the nanofibrous vs. the polypropylene membrane and the hyphenated SLM-CE method with the nanofibrous membrane was characterized by good repeatability (RSD ≤ 11.3%), linearity (r2 ≥ 0.9953; 0.5-20 mg/L), sensitivity (LOD ≤ 0.4 mg/L) and transfer (27-126%) of the basic drugs.
Keywords: design vybavení; senzitivita a specificita; Reproducibility of Results; Nanofibers; reprodukovatelnost výsledků; Models, Chemical; léčivé přípravky; lidé; elektroforéza kapilární; chemické modely; Equipment Design; Membranes, Artificial; Pharmaceutical Preparations; Linear Models; membrány umělé; Humans; nanovlákna; Sensitivity and Specificity; lineární modely; Electrophoresis, Capillary